PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP KETERAMPILAN SOSIAL DI KELAS TINGGI MATA PELAJARAN PENDIDIKAN PANCASILA - Ikhsan, MT Hartono; Isda Ayu Nur Fasya; Ai Hayati Rahayu; Encep Iman Hadi Sunarya (JESA-Jurnal Edukasi Sebelas April, 2026)
Students’ social skills are often underdeveloped in upper elementary classes, particularly in Pancasila Education learning, which tends to be one-way and teacher-centered. This condition results in students’ limited ability to interact, collaborate, and express their opinions effectively. Therefore, this study aims to investigate the effect of the cooperative learning model Snowball Throwing on improving students’ social skills through a quantitative approach using a pre- experimental method with a one-group pretest-posttest design. The study was conducted at SDN Jatihurip with a saturated sample of 23 fifth-grade students. The research instrument was a social skills questionnaire consisting of 24 Likert-scale statements, administered before and after the treatment. Data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, and effect size calculation. The results showed an increase in the average score from 54.78 to 80.57, with a significance value of 0.001 (p < 0.05) and an effect size of 2.943. Based on these findings, it can be concluded that the Snowball Throwing cooperative learning model is effective in improving students’ social skills and can be implemented as an active, collaborative, and meaningful learning strategy in Pancasila Education at the elementary school level.